Organizational behavior : tools for success - Phillips, Jean M.; Gully, Stanley M. (Australia : Cengage Learning Asia Pte Ltd, 2014)
In this edition we updated many of the chapter opening real world challenges and case studies to keep the examples current.
The organizational behavior context -- Individual effectiveness -- Social interactions -- Groups, teams, and leadership -- Organizational design, organizational change, and career management.
Includes bibliographical references and index.
Keywords: ORGANIZATIONAL BEHAVIOR